Bilateral tax treaties: is sufficient relief provided in triangular tax situations? - Uys, Odette (My University, 2014)
With the international platform for cross border investment and economic development growing year on year at a steady pace, it has become apparent that bilateral income tax treaties do not always operate effectively in multilateral tax situations. Global transactions involving more than two states are certainly not uncommon and it could be said that the most fundamental issue in international taxation is double taxation resulting from the taxing rights of different tax jurisdictions that ‘overlap’ with regard to, generally speaking, one taxpayer or one declared income stream. Multilateral tax situations, commonly known as triangular cases, occur where tax incidence on a particular stream of income is triggered in three countries. These situations typically arise where a person who is a tax resident in two respective countries for tax purposes (a dual resident), or a person who is a tax resident in one country and has a permanent establishment in another, is earning revenue of which the source is in a third country. Taxing rights and jurisdictions of the three countries involved could potentially be in conflict with each other and therefore such situations may bring about lawful international triangular taxation or double taxation which will inevitably discourage enterprises from continuing investment and development internationally. Broad multilateral treaties in the income tax arena are not common1, and most treaties are still of a bilateral nature, i.e. generally addressing tax scenarios where only two specific countries are involved. The Organisation for Economic Cooperation and Development’s (’the OECD’)Model Tax Convention states this: There are no reasons to believe that the conclusion of a multilateral tax convention involving all Member countries could now be considered practicable. The Committee therefore considers that bilateral conventions are still a more appropriate way to ensure the elimination of double taxation at the international level.2
Thesis (M.Com. (Taxation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2014.
Keywords: Bilateral tax treaties; Multilateral taxation; Triangular cases; International double taxation; Double tax agreements; Cross-border investment; Tax avoidance